Anti-hypoxic Effect of Polysaccharide Extract of Brown Seaweed Sargassum dentifolium in Tongue Squamous Cell Carcinoma - Gamal-Eldeen, Amira M.; Raafat, Bassem M.; Alrehaili, Amani A.; El-Daly, Sherien M.; Hawsawi, Nahed; Banjer, Hamsa J.; Raafat, Eman M.; Almehmadi, Mazen M. (Frontiers in Nutrition, 2022)
Sargassum dentifolium, (Turner) C. Agarth, 1820, is an edible brown alga collected from red seashores, Egypt. Oral tongue squamous cell carcinoma (OTSCC) is an aggressive malignancy. Hypoxia leads to chemotherapeutic resistance. This work aimed to explore the anti-hypoxia effect of water-soluble polysaccharide fractions of S. dentifolium (SD1–SD3) in CAL-27 OTSCC cells. Cell cytotoxicity assay (MTT); cell death mode (DNA staining); total hypoxia (pimonidazole), HIF-1α (ELISA and immunocytochemistry), HIF-1β (ELISA), and hsa-miRNA-21-5p and hsa-miRNA-210-3p (qRT-PCR) were investigated. SD1 and SD2 showed a cytotoxic effect due to apoptosis. SD2 and SD3 decreased total cell hypoxia, inhibited miR-210 (p < 0.001 and p < 0.01), miR-21 (p < 0.01 and p < 0.05), and HIF-1α (p < 0.01 and p < 0.05), respectively. However, only SD3 suppressed HIF-1β (p < 0.05). In conclusion, SD2 showed a potential anti-hypoxia effect through amelioration of HIF-1α regulators, which may help in decreasing hypoxia-induced therapeutic resistance.